Cellular Dedifferentiation and Regenerative Medicine - Fu, Xiaobing (Springer Berlin Heidelberg, 2018)
This book focuses on the contribution of cell dedifferentiation to the regenerative process in all body systems, as well as its underlying molecular mechanisms and applications. The book is divided into four parts, the first of which addresses the history of cell dedifferentiation and regenerative medicine. In turn, Part II compares three routes by which cells change their phenotype: dedifferentiation, transdifferentiation, and reprogramming. Part III includes an extensive review of cell dedifferentiation events in all nine body systems for lower organisms and mammalians, respectively. The final part reviews the relationship between cell dedifferentiation and the development of cancer and several other diseases, while also outlining the prospects of and future research directions in cell dedifferentiation and regenerative medicine. The main purpose of the book is to underline the importance of cell dedifferentiation in stem cell and regenerative medicine by providing a systematical review of dedifferentiation in all body systems, together with the latest reliable evidence.